1989
DOI: 10.1271/bbb1961.53.2553
|View full text |Cite
|
Sign up to set email alerts
|

Thermal aggregation of cod (Gadus morhua) muscle proteins using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide as a zero length cross-linker.

Abstract: The initial stages of thermally-induced aggregation of cod myofibrils resulted from noncovalent intermolecular cross-linking as demonstrated by SDSelectrophoresis. The nature of the noncovalent bonds was studied by introducing a zero length cross-linker, l-ethyl-3-(3-dimethylamino propyl) carbodiimide (EDC). This allowed the examination of the noncovalent interactions by SDS electrophoresis and quantitative densitometry. Initially, during heating, about 50 % of the myosin heavy chain was cross-linked to form a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
3
19
1
Order By: Relevance
“…It must be remarked that albeit fitted responses suggest a lower pH value, best experimental data was attained in the 11th run, pH = 4.94 (Table 3). Moreover, results contradict the interpretation given by some authors [31] that the disappearance of protein bands from SDS-PAGE gels of cod myofibrils illustrated protein aggregation and was not function of EDC reactivity. Protein aggregation does not explain, for instance, the GS response as a function of pH.…”
Section: Texture Measurementscontrasting
confidence: 99%
“…It must be remarked that albeit fitted responses suggest a lower pH value, best experimental data was attained in the 11th run, pH = 4.94 (Table 3). Moreover, results contradict the interpretation given by some authors [31] that the disappearance of protein bands from SDS-PAGE gels of cod myofibrils illustrated protein aggregation and was not function of EDC reactivity. Protein aggregation does not explain, for instance, the GS response as a function of pH.…”
Section: Texture Measurementscontrasting
confidence: 99%
“…Holding fish muscle proteins, after comminution with salt, at temperatures below 40 "C before a subsequent heating at higher temperatures resulted in an ordered structure of the protein molecules, which consequently produced stronger gels (Lanier and others 1982). Previous studies indicated that myosin was the major protein affecting the gel-forming ability of fish during setting (Gill andConway 1989, Sano andothers 1988). Calcium dependent endogenous TGase was also reported to be responsible for the unique setting ability of surimi (Seki and others 1990; b a t h and others 1992; Lee and others 1997b).…”
Section: Discussionmentioning
confidence: 96%
“…Cheftel and Culioli (1997) reported that a large increase solubilization of myofibrillar proteins was observed when the applying pressures were between 150 and 300 MPa. It would appear virtually certain that for fish proteins, the setting effect uniquely involves non-disulfide cross-linking of myosin (Gill and Conway 1989;Sano et al 1990). The high breaking strain but low breaking force of pressure-induced gels was contributed to constitution of hydrogen bonds, hydrophobic interactions but the small amount of disulfide bonds.…”
Section: Protein Solubilitymentioning
confidence: 99%